ANALISIS BIAYA OPERASIONAL KENDARAAN BERDASARKAN KECEPATAN RATA-RATA PERJALANAN DI JALAN MAJAPAHIT KOTA MATARAM - HASYIM HASYIM; ROHANI ROHANI (GANEC SWARA, 2024)
The city of Mataram, the center of trade, offices, and education, experienced an increase in population and vehicles. The 2023 data recorded 441.147 thousand residents and 385,579 motor vehicles. The increase in traffic volume on road Majapahit has an impact on traffic performance and vehicle operating costs. The study entitled " Analysis Of Vehicle Operational Costs Based On Average Travel Speed On Jalan Majapahit Mataram City" was conducted to further understand the condition of road section performance and the Operating Cost of Vehicles passing through the road. The MKJI method is a calculation standard used to analyze the performance of road sections, assess capacity and service levels, based on traffic volume and road geometry. while to calculate BOK (Vehicle Operating Costs) used an equation method developed by the PCI 1989 method to measure vehicle costs, including fixed costs and non-fixed costs, which are influenced by the average speed of travel. The results of the study on the Majapahit road section show the service level of the Majapahit road section in category C. For the calculation of the free flow speed, namely 52.68 km / h (east) and 49.10 km / h (west). The speed of the eastbound peak clock is 48 km/h and the westward is 42 km/h. While the calculation results of BOK Group I (Eastward) Free Flow Speed Rp1.049,- / km, Peak Hour Speed Rp1.082,- /km. Group I (West) Free Flow Speed Rp1.072,- /km, Peak Hour Speed Rp1.163,- /km. Group IIA (Eastward) Peak Hour Speed Rp2.921,- /km, Peak Hour Speed Rp3.007,- /km. Group IIA (Westward) Free Flow Speed Rp2.980,- /km, Peak hour speed Rp3.235,- /km